RESILIENCE PATTERNS OF FARMERS AFTER THE ERUPTION OF MOUNT SINABUNG IN KUTARAYAT VILLAGE, NAMAN TERAN SUB-DISTRICT, KARO REGENCY - Br Sitepu, Sinarisa; Badaruddin, Badaruddin; Sitorus, Henri; Marhaeni Munthe, Hadriana; Sitorus, Henry (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
The community in Kutarayat Village has been the victim of the eruption of Mount Sinabung for years, from the first eruption that occurred in 2010 until 2021. During this vulnerable period, the people of Kutarayat Village had to evacuate several times. The majority of the community's livelihoods are as farmers, making it a significant challenge for those affected by the eruption of Mount Sinabung. Therefore, this research aims to understand how farmers perceive the eruption of Mount Sinabung, as well as the socio-economic efforts they have made after the cruption, and to identify the resilience patterns that have emerged post-eruption. The research method used in this study is qualitative and conducted in Kutarayat Village, Naman Teran District, Karo Regency. Data collection techniques include observation and in-depth interviews with informants. The results of the study found that, generally, farmers perceive the eruption of Mount Sinabung from two perspectives: positive and negative. The economic resilience efforts made by farmers include meeting family needs while evacuating, cleaning, and repairing agricultural land post-eruption, ensuring water supply for agriculture, and utilizing volcanic mud. There are three patterns of economic resilience among farmers in Kutarayat Village: first, economic resilience pattern with the same livelihood, second, economic resilience pattern by adding or changing the main livelihood, and third, economic resilience pattern by renting agricultural land in other villages.